2020
DOI: 10.1590/s2175-97902019000418345
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro and in vivo investigation of biological activities and phenolic analysis of Helichrysum plicatum subsp. plicatum

Abstract: In Turkey, Helichrysum genus is represented by 26 taxa belonging to 20 species in Turkish flora of which 14 ones are endemic to Turkey. The aerial parts of Helichrysum plicatum subsp. plicatum are used kidney stones, kidney and stomach ailments. The extraction procedures and solvents are important step in processing of bioactive constituents from the plant materials. Therefore, the aim of this study was to evaluate in vitro antioxidant, antimicrobial, anti-urease, anticholinesterase and in vivo antiinflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Antioxidants neutralize the free radical character of DPPH * by either transferring an electron or a hydrogen atom [34]. The reducing potential of compounds could indicate the possible antioxidant property [35]. Results of the present study indicated a gradual increase in scavenging activity with the increase of extract concentration.…”
Section: Dpph* Radical Scavenging Potential Of Extractsmentioning
confidence: 54%
“…Antioxidants neutralize the free radical character of DPPH * by either transferring an electron or a hydrogen atom [34]. The reducing potential of compounds could indicate the possible antioxidant property [35]. Results of the present study indicated a gradual increase in scavenging activity with the increase of extract concentration.…”
Section: Dpph* Radical Scavenging Potential Of Extractsmentioning
confidence: 54%
“…It is known that extracts of H. plicatum have remarkable antioxidant, antimicrobial, and cytotoxic activities (Demir et al 2009;Tatlı et al 2009;Apaydın Yıldırım et al 2017;Taşkın et al 2020). In the literature, it is reported that the composition of H. plicatum is rich in flavonoids (Kulevanova et al 2000;Acet et al 2019;Güneş et al 2019).…”
Section: Discussionmentioning
confidence: 99%